2022
DOI: 10.3390/ijms23073634
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Effects of Animal Toxins: Is There a Way to Drugs?

Abstract: Viruses infect all types of organisms, causing viral diseases, which are very common in humans. Since viruses use the metabolic pathways of their host cells to replicate, they are difficult to eradicate without affecting the cells. The most effective measures against viral infections are vaccinations and antiviral drugs, which selectively inhibit the viral replication cycle. Both methods have disadvantages, which requires the development of new approaches to the treatment of viral diseases. In the study of ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…Some linear venom peptides are capable of exerting antiviral activity, including activities against influenza viruses [ 25 , 26 , 27 ]. Given that the A-family peptides showed no toxicity toward MDCK II cells, we infected these cells with influenza viruses (H1N1, H3N2 or B-Malaysia (B-Mal)) and determined whether or not the A-family peptides possess antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…Some linear venom peptides are capable of exerting antiviral activity, including activities against influenza viruses [ 25 , 26 , 27 ]. Given that the A-family peptides showed no toxicity toward MDCK II cells, we infected these cells with influenza viruses (H1N1, H3N2 or B-Malaysia (B-Mal)) and determined whether or not the A-family peptides possess antiviral activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several scientists have studied the antiviral activity of PLA2 from the venoms of different species of snakes against several human viruses, including Encephalomyocarditis virus (EMCV), Influenza A (IAV), Coxsackie virus B3 (CVB3), HIV, Dengue virus (DENV), Hepatitis C virus (HCV), Herpes simplex virus (HSV), Japanese encephalitis (JEV), Mayaro virus (MAYV), Middle East respiratory syndrome coronavirus (MERS), SARS-CoV-2 virus, as well as they illustrated the mechanisms of inhibition action against several viruses (Muller et al 2012 , 2014 ; Cecilio et al 2013 ; Russo et al 2014 ; Shimizu et al 2017 ; Rodrigues et al 2019 ; Brenes et al 2020 ; Teixeira et al 2020 ; Siniavin et al 2021 , 2022 ; Utkin et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal venoms are rich in active biological compounds [ 63 ] and several toxins from different venomous and poisonous animals, whether aquatic or terrestrial, have already had their antiviral potential determined against many types of viruses. For dengue virus, a PLA 2 from Bothrops leucurus snake venom was able to decrease amounts of viral RNA [ 64 ]; similarly, a PLA 2 from honey bee Apis mellifera also prevented intracellular release of the viral capsid protein of human immunodeficiency virus (HIV), and hepatitis C virus (HCV), among others, suggesting it blocks viral entry into cells [ 1 , 65 ]. In 2011, Li et al observed that the optimized toxin mucroporin from Lychas mucronatus scorpion venom, mucroporin-M1, was able to perform a potent antiviral activity against measles, influenza H5N1, and SARS-CoV viruses, demonstrating that toxins could be prototypes of new antiviral drugs [ 66 ].…”
Section: Crosstalk Of Animal-derived Toxins and Covid-19mentioning
confidence: 99%
“…A virus is a non-cellular agent with nucleic acid surrounded by a protein coating (some may also have a lipid envelope over the capsid) and which can only reproduce within host cells [ 1 ]. Virus-borne diseases affect millions of people every year, causing mild infections to severe complications and deaths, such as Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV-AIDS) and Coronavirus Disease 2019 (COVID-19) [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%